Occerrences of microcystis spp. and microcysting in some cyanobacterial blooms in freshwater bodies in Vietnam - Lien, Nguyen Thi Thu; Trang, Pham Nguyen Thu; Hoa, Tran Thi My (VNU Journal of Science: Natural Sciences and Technology, 2010)
Abstract